DIAGNOSTICS OF DOG ACUTE PANCREATITIS: CLINICAL CASE FROM VETERINARY PRACTICE - Chekantseva, D. Yu.; Kanivets, N. S.; Karysheva, L. P.; Bobrova, V. V. (Scientific Progress & Innovations, 2020)
Pancreatitis is an inflammation of the pancreas, and dogs most often have an acute course. It is characterized by vomiting, colic, squealing, unnatural posture at standing, and sometimes diarrhea. The research was conducted in the Veterinary Medicine Clinic of the city of Mykolaiiv. The aim of the research was to analyze the diagnostics of dog acute pancreatitis. We investigated and presented a case from clinical practice of a dog of boxer breed, 5 years old having body weight of17 kg and suffering from acute pancreatitis. Different diagnostic methods for revealing the disease have been described. As a result of the conducted examination the data of the patient's anamnesis were taken into account. The main reason of the disease was identified - uncontrolled feeding (unlimited access to the feeder, containing food), which causes excessive consumption of food by the dog. Changes in the dog’s clinical condition were identified and characteristic signs were registered (hyperthermia, tachypnea, tachycardia, untypical posture at standing, and weakness). During hematological studies, inflammatory anemia and moderate leukocytosis were diagnosed. The analysis of biochemical indicators revealed hyper-enzymia of alpha-amylase almost twice as high as the standard for dogs. The increase of activity in the blood serum of this enzyme was registered at damaging pancreas cells, especially in case of acute pancreatitis. At the same time, bilirubinemia and transaminases (ALT and AST) increased activity were diagnosed. Ultra-sonographic examination detected changes in the pancreas size and structure. At sonography, the visualization of the organ was unclear and hypo-echogenic, which confirmed the swelling of its tissues. The results obtained by us should be taken into account by practicing veterinary doctors in differentiating the pancreas diseases.